Acceptability of Property Technology (PropTech) on Property Management Practice in Cross River State, Nigeria - Ewah, M. A.; Effiong, J. B. (International Journal of Real Estate, 2026)
This study examined the acceptability of Property Technology (PropTech) in property management practice within Calabar Metropolis, Cross River State, focusing on residential and commercial properties. The study adopted a descriptive survey design and purposive sampling technique, targeting a population of 22 experienced property professionals. Data was collected through administration of structured questionnaire and interviews and analyzed using Multiple Regression Analysis. The findings revealed a significant effect of PropTech on traditional property management practice. The study found widespread awareness of PropTech innovations with digital platforms and industry events being the main sources of knowledge. Cost, cultural adaptation, and technical skills were identified as key factors influencing adoption while PropTech solutions were generally more effective than traditional methods. Online platforms dominated adoption with advanced tools showing moderate but growing use. Based on these findings, the study recommends targeted training programs, financial support and incentives, peer-to-peer knowledge sharing, public awareness campaigns and the institutionalization of PropTech education within professional certification programs to facilitate sustainable and inclusive integration. These measures aimed to overcome barriers such as cost and limited knowledge and promote the effective use of PropTech to enhance property management performance in Calabar Metropolis.
Keywords: PropTech; Residential Property; Commercial Property; Acceptability; Management